A. 4
B. - 2
C. 2
D. - 4
B
Do \(A\left( {a;b} \right) \in d \Rightarrow a - b - 3 = 0 \Leftrightarrow a = 3 + b\). Vậy \(A\left( {3 + b;b} \right)\)
\(\begin{array}{l}
d\left( {A;\Delta } \right) = \sqrt 5 \Leftrightarrow \frac{{\left| {2\left( {3 + b} \right) - b + 1} \right|}}{{\sqrt {{2^2} + {{\left( { - 1} \right)}^2}} }} = \sqrt 5 \Leftrightarrow \left| {b + 7} \right| = 5 \Leftrightarrow \left[ \begin{array}{l}
b + 7 = 5\\
b + 7 = - 5
\end{array} \right.\\
\Leftrightarrow \left[ \begin{array}{l}
b = - 2 \Rightarrow a = 1\\
b = - 12 \Rightarrow a = - 9
\end{array} \right.
\end{array}\)
Vì \(a>0\) nên \(a=1, b=-2\). Do đó \(P=ab=-2\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247